Citizens, experts and the environmental impact statement: procedural structures and participatory boundaries - Davidson, Casey, author; Carolan, Michael, advisor; Taylor, Pete, committee member; Feige, Mark, committee member (Colorado State University. Libraries, 2010)
This thesis is a qualitative case-study of environmental management and decision-making as practiced by the Rocky Mountain National Park (RMNP) in accordance with the environmental impact statement (EIS) process. Because there has been little empirical study of the EIS process despite criticisms that it has generally failed to both meaningfully engage citizens in governance and produce environmental outcomes consistent with the substantive aims of the National Environmental Policy Act (NEPA), this study provides an in-depth and longitudinal analysis of the ways in which EIS procedures impacted the collaborative planning and development of RMNP's elk and vegetation management EIS. To explore how EIS procedures affect environmental planning and management, I use RMNP's archival records to reconstruct the life-cycle of the planning process and the events, processes, actors and considerations that played a role in shaping the trajectory and outcomes of planning. Furthermore, archival data is supplemented with semi-structured interviews to document how the management issue with elk and vegetation was constructed and shaped by the managerial imperatives of the park, the efforts and concerns of interagency collaborators and citizens, and by EIS protocol as it was interpreted by the interagency team and influential upon planning considerations, decisions and outcomes. The findings of this study contribute to an understanding of the EIS as a decision-making procedure and also provide some empirical support for scholarly criticisms of the EIS. However, these findings also suggest that the procedure's affects on environmental governance are more complex than currently theorized and difficult to disentangle from the constraints that divergent interagency orientations, interests and policies, and divisive and impassioned views among citizens pose for environmental governance. Therefore, this study is as much as case-study of interagency collaboration and citizen participation in the context of environmental management in the contemporary U.S. as it is a case-study of the EIS process. For this reason, my discussion of how conflicts and constraints emerged during planning, were addressed by interagency actors, and subsequently impacted public participation and managerial outcomes provides insights useful for scholars of environmental management or governance as well as practitioners who encounter these scenarios both within and outside of the EIS.
Covers not scanned.
Keywords: Environmental impact statements -- Colorado -- Rocky Mountain National Park -- Case studies; Environmental impact statements -- United States -- Case studies